111k views
2 votes
Find (f ∘ g)(-6) when f(x) = 9x + 2 and g(x) = -9x2 - 2x + 1.

A.573

B.-2797

C.-24,231

D.605

User JackD
by
5.7k points

1 Answer

1 vote

Given that the two functions are
f(x)=9x+2 and
g(x)=-9x^2-2x+1

We need to determine the value of
(f \circ g)(-6)

The value of
(f \circ g)(x):

The value of
(f \circ g)(x) can be determined using the formula,


(f \circ g)(x)=f[g(x)]

Substituting
g(x)=-9x^2-2x+1 in the above formula, we get;


(f \circ g)(x)=f[-9x^2-2x+1]

Now, substituting
x=-9 x^(2)-2 x+1 in the function
f(x)=9x+2, we get;


(f \circ g)(x)=9(-9x^2-2x+1)+2


(f \circ g)(x)=-81x^2-18x+9+2


(f \circ g)(x)=-81x^2-18x+11

Thus, the value of
(f \circ g)(x) is
(f \circ g)(x)=-81x^2-18x+11

The value of
(f \circ g)(-6):

The value of
(f \circ g)(-6) can be determined by substituting x = -6 in the function
(f \circ g)(x)=-81x^2-18x+11

Thus, we have;


(f \circ g)(-6)=-81(-6)^2-18(-6)+11


(f \circ g)(-6)=-81(36)-18(-6)+11


(f \circ g)(-6)=-2916+108+11


(f \circ g)(-6)=-2797

Thus, the value of
(f \circ g)(-6) is -2797

Hence, Option B is the correct answer.

User Willwsharp
by
5.3k points